Clinical and economic burden of pre‐emptive therapy of cytomegalovirus infection in hospitalized allogeneic hematopoietic cell transplant recipients. Issue 1 (3rd September 2019) - El Haddad, Lynn; Ghantoji, Shashank S.; Park, Anne K.; Batista, Marjorie V.; Schelfhout, Jonathan; Hachem, Jack; Lobo, Yadira; Jiang, Ying; Rondon, Gabriela; Champlin, Richard; Chemaly, Roy F.
Abstract: Cytomegalovirus (CMV) infection remains a major complication after allogeneic hematopoietic cell transplantation (allo‐HCT). We conducted a retrospective study to determine the clinical and economic burden of pre‐emptive therapy (PET) for CMV infection in 100 consecutive hospitalized adult CMV positive serostatus allo‐HCT recipients and compared their hospitalization cost with allo‐HCT recipients hospitalized with graft vs host disease without CMV infection (control group) and across 19 US cancer centers for hospitalized patients with CMV infection between 2012 and 2015 (Vizient database). A total of 192 CMV episodes of PET for CMV infection occurred within 1 year post‐HCT. PET consisted of ganciclovir (41% of episodes), foscarnet (40%), and valganciclovir (38%) with the longest average length of stay in foscarnet‐treated patients (41 days). The average direct cost per patient admitted for PET was $116 976 (range: $7866‐$641 841) compared with $12 496 (range: $2004‐$43 069) in the control group ( P  < .0001). The total direct cost per encounter was significantly higher in patients treated with foscarnet and had nephrotoxicity ($284 006) compared with those who did not ($112 195). The average cost amongst the 19 US cancer centers, including our institution, was $42 327 with major disparities in cost and clinical outcomes. PET for CMV infection is associated with high economic burden in allo‐HCT recipients. Highlight: The average direct cost for allo‐HCT recipients hospitalized for PET for CMV infection was higher than that of recipients hospitalized for GVHD. There are major clinical and economic disparities of CMV infections in allo‐HCT recipients across 19 U.S. cancer centers.